Apulose bowenóide: um caso clínico - Furtado, Contaça; Antônio, Ana Maria; Bajanca, Rui; Costa, Maria Manuel; Feio, Ana Barata; Soares, A. Pinto (Brazilian Journal of Sexually Transmitted Diseases, 1998)
We describe a parielll wiih bowenoid papulosis of lhe inguino-scroral fold. confirrned by hiscopachologic findings and by idenrificarion of Human Papilomavirus 16 in lesiona skin.